2021
DOI: 10.1155/2021/1448206
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomic Investigation of Eugenol on Colorectal Cancer Cell Line HT-29 by Modifying the Expression of APC, p53, and KRAS Genes

Abstract: Colorectal cancer is one of the most lethal cancers with a high mortality rate. Chemotherapy results in drug resistance in some cases; hence, herbal medicines are sometimes used in adjunct with it. Eugenol has been reported to have anti-inflammatory, antioxidant, and anticancer properties. Metabolomics is a study of metabolic changes within an organism using high-throughput technology. The purpose of this research was to investigate the anticancer effects of eugenol and variations in p53, KRAS, and APC gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Colon cancer is a multistage disease characterized by successive changes in various genes, including Apc and Kras , leading to changes in CRC signaling pathways such as the APC Wnt/β-catenin and K-RAS [ 43 ]. As Apc and Kras are frequently mutated in CRC, targeting these genes could provide insights into the effects of bioactive compounds in CRC treatment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is a multistage disease characterized by successive changes in various genes, including Apc and Kras , leading to changes in CRC signaling pathways such as the APC Wnt/β-catenin and K-RAS [ 43 ]. As Apc and Kras are frequently mutated in CRC, targeting these genes could provide insights into the effects of bioactive compounds in CRC treatment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the intensity of the colored formazan product, which has an absorbance near 570 nm, the assay enabled us to assess the viability of cells treated with various concentrations of Eug. The concentrations used in this study (0.1 mM, 0.25 mM, 0.5 mM, 0.75 mM, and 1 mM) were chosen based on a comprehensive review of the currently available literature [ 27 , 28 , 29 , 30 ]. Several in vitro studies have evaluated eugenol’s cytotoxicity in blood, breast, skin, cervical, and colon cell lines via various mechanisms of action [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are aligning with the available literature on this topic. Ghodousi-Dehnavi E. et al showed that Eug has the ability to increase the expression of the p53 tumor suppressor gene and decrease the expression of the KRAS oncogene gene in colon adenocarcinoma cells [ 30 ]. Moreover, Fathy M. and colleagues showed that Eug produces a decrease in the expression of the Bcl-2 gene, while increasing the expression of the Bax gene in HeLa cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the regulatory effect of linalool on the oxidative response was beneficial for the treatment of colon cancer; it was confirmed that cellular apoptosis was induced by promoting the production of hydroxyl radicals and 4-HNE (a marker of oxidative stress due to increased lipid peroxidation) ( Iwasaki et al, 2016 ). Moreover, some studies focused on the inhibitory effects of eugenol, isoeugenol, and dihydrodiiisoeugenol on colon cancer cells, showing that their anti-cancer mechanisms involve the regulation of metabolic pathways, apoptosis/metastasis-related gene expression, and the activation of endoplasmic reticulum stress-induced inhibition of autophagy ( Li et al, 2021a ; Ghodousi-Dehnavi et al, 2021 ; Bilgin et al, 2023 ). In above studies, Iwasaki et al ( Iwasaki et al, 2016 ) and Li et al ( Li et al, 2021b ) used the tumor xenograft model in their experiments, while evidence from other studies mainly came from cell experiments.…”
Section: Research Progress On Metabolites Of Sishen Pill In the Treat...mentioning
confidence: 99%